2022
DOI: 10.21067/jbpd.v6i1.6617
|View full text |Cite
|
Sign up to set email alerts
|

Analisis Dampak Pengembangan dan Implementasi Kurikulum MBKM Terhadap Kepuasan Mahasiswa FIP UNIKAMA

Abstract: The purpose of this study was to analyze the internal student satisfaction of Study Programs within the Faculty of Education. This research is a quantitative descriptive study with a survey method using a questionnaire as a data collection tool. The survey results show that the average student satisfaction in the Faculty of Education, Universitas PGRI Kanjuruhan Malang shows a very good category. Tangibles dimension has an average percentage of 40.33% with a very good category. Responsiveness with an average p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 3 publications
0
7
0
1
Order By: Relevance
“…In the cognitive aspect, MBKM activities can support collaborative and participatory learning activities and improve students' analytical skills and problem-solving abilities (Anggadini et al, 2022). The survey done in the Faculty of Education, Universitas PGRI Kanjuruhan Malang, shows an outstanding category for the average student satisfaction for the MBKM program (Chrisyarani et al, 2022). Another positive aspect was that online learning turned out to be very supportive of the implementation of the MBKM program (Krishnapatria, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…In the cognitive aspect, MBKM activities can support collaborative and participatory learning activities and improve students' analytical skills and problem-solving abilities (Anggadini et al, 2022). The survey done in the Faculty of Education, Universitas PGRI Kanjuruhan Malang, shows an outstanding category for the average student satisfaction for the MBKM program (Chrisyarani et al, 2022). Another positive aspect was that online learning turned out to be very supportive of the implementation of the MBKM program (Krishnapatria, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…The MBKM program is an opportunity to collaborate between educational institutions and the Business and Industry World as needed, meeting demands (Andari et al 2021); (Chrisyarani, et al, 2022). Learning in the Kampus Merdeka is one of the manifestations of student-centered learning (Chrisyarani, et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…The MBKM program is an opportunity to collaborate between educational institutions and the Business and Industry World as needed, meeting demands (Andari et al 2021); (Chrisyarani, et al, 2022). Learning in the Kampus Merdeka is one of the manifestations of student-centered learning (Chrisyarani, et al, 2022). The MBKM program is implemented in eight forms of learning activities to achieve the KPI (Key Performance Indicators) achievement target (Maryanti et al 2021); (Chrisyarani, et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another research by (Tuti Marjan Fuad, 2021) found that the MBKM curriculum is expected to facilitate students to develop their potential according to their passions and talents. The research was also conducted (Chrisyarani et al, 2022). Students were satisfied with implementing the independent learning curriculum as a way of self-development to prepare graduates for the world of work.…”
Section: Introductionmentioning
confidence: 99%